The Protection of International Humanitarian Law against Child Sexual Violence in Armed Conflict: A Case Study of Sudan - Tesalonika David; Indah Sri Utari (Law Research Review Quarterly, 2026)
This study examines the protection of international humanitarian law for child victims of sexual violence in Sudan's armed conflict, particularly in the context of the use of sexual violence as a weapon of war by the Rapid Support Forces (RSF) since April 2023. Using normative legal research methods with legislative, conceptual, and comparative approaches, this study analyzes applicable international legal instruments, international criminal tribunal jurisprudence, and available law enforcement mechanisms. The results of the study show two main findings. First, the normative framework of international humanitarian law including the 1998 Rome Statute, the 1949 Geneva Convention, the 1989 Convention on the Rights of the Child, and the UN Security Council Resolutions have provided a juridically adequate legal basis for establishing criminal accountability against RSF perpetrators through the ICC mechanism based on the referral jurisdiction of Resolution 1593 (2005), as reinforced by the precedent of the Ali Kushayb ruling (October 2025). Second, effective protection for child victims of sexual violence faces serious implementation gaps due to four structural barriers: state non-cooperation in the execution of arrest warrants, limitations of UN Security Council mechanisms, barriers to proof on the ground, and the inadequacy of Sudan's national justice system. The study concludes that the continued impunity is not a reflection of the inadequacy of legal norms, but rather a failure of the political will of the international community to implement them consistently.